STRATEGI COPING STRES DALAM PSIKOLOGI DEWASA AWAL: SEBUAH REVIEW LITERATUR TERHADAP MODEL DAN TEMUAN EMPIRIS - Dyastuti, Irma Suwarning (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Stress is a common psychological condition experienced by individuals in early adulthood, a developmental phase characterized by increasing demands related to education, employment, and social relationships. Individuals’ ability to manage stress is strongly influenced by the coping strategies they employ. This article aims to examine and analyze stress coping strategies among early adults based on findings from psychological literature. The method used in this study is a literature review, focusing on national and international journal articles published between 2020 and 2025. The literature was collected from databases such as Google Scholar and Garuda using relevant keywords related to stress coping and early adulthood. The results of the review indicate that stress coping strategies in early adulthood can be broadly categorized into problem-focused coping and emotion-focused coping, with their application influenced by individual characteristics, social support, and environmental context. The literature also highlights that adaptive coping strategies contribute positively to mental health and psychological well-being, while maladaptive coping strategies may increase the risk of prolonged stress. This article is expected to provide a comprehensive conceptual understanding of stress coping strategies and serve as a reference for future research and psychological interventions targeting early adults. ABSTRAK Stres merupakan fenomena psikologis yang umum dialami individu pada fase dewasa awal, seiring dengan tuntutan perkembangan seperti pendidikan, pekerjaan, dan relasi sosial. Kemampuan individu dalam menghadapi stres sangat dipengaruhi oleh strategi coping yang digunakan. Artikel ini bertujuan untuk mengkaji dan menganalisis strategi coping stres pada individu dewasa awal berdasarkan temuan-temuan dalam literatur psikologi. Metode yang digunakan adalah literature review dengan menelaah artikel ilmiah nasional dan internasional yang diterbitkan dalam rentang tahun 2020–2025. Sumber literatur diperoleh melalui basis data Google Scholar dan Garuda dengan kata kunci yang relevan dengan coping stres dan dewasa awal. Hasil kajian menunjukkan bahwa strategi coping stres pada dewasa awal dapat diklasifikasikan ke dalam dua kategori utama, yaitu problem-focused coping dan emotion-focused coping, yang penggunaannya dipengaruhi oleh faktor individu, dukungan sosial, serta konteks lingkungan. Literatur juga menunjukkan bahwa strategi coping yang adaptif berkontribusi terhadap kesehatan mental dan kesejahteraan psikologis individu dewasa awal, sementara coping maladaptif berpotensi meningkatkan risiko stres berkepanjangan. Artikel ini diharapkan dapat memberikan pemahaman konseptual yang komprehensif mengenai strategi coping stres serta menjadi rujukan bagi pengembangan penelitian dan intervensi psikologis pada kelompok dewasa awal.